Mileage of Motor Vehicles in 2004 Higher Than Ever Before - Hartmut Kuhfeld; Uwe Kunert (Weekly Report, 2005)
2003 saw a slight decline in the mileage of vehicle kilometers driven annually by all German road passenger and freight vehicles. This development did not continue in 2004; instead the mileage, at 697 billion vehicle kilometers, was higher than ever before, despite the fact that fuel prices continued to rise. Where freight vehicles are concerned, the number of vehicles on the road hardly changed as compared to 2003; the volume of goods to be transported only rose marginally. Since, however, transport distances increased, the mileage of German freight and semitrailer trucks was 1.3% higher in 2004 as compared to the previous year. The mileage of passenger cars registered in Germany even increased by 2.3% to 591 billion vehicle kilometers. The decline in 2003 was clearly not a shift in the trend, but rather one of the short-term adjustment reactions by consumers, as has often occurred in the past. Average consumption of motor vehicles decreased only marginally in the past year; total consumption of fuel in the traffic sector increased by 1.6%. The amount of the climate-relevant CO2 gas emitted even rose by 1.8%, since the increase of consumption was larger for diesel fuel with higher CO2 exhaust per liter than gasoline.
Keywords: 330